Clinical experience with lanreotide for the treatment of acromegaly. Issue 2 (March 2012) - Roemmler, Josefine; Schopohl, Jochen
Acromegaly is a rare disease, characterized in adults by its distinctive appearance of facial dysmorphism and swollen fingers. It is caused by an overproduction of growth hormone (GH) in more than 99% of patients and in nearly all cases is due to a pituitary adenoma. If surgical resection of the adenoma is not effective, medical treatment is usually the next treatment option. The most commonly used medications are the somatostatin analogues octreotide and lanreotide. Lanreotide is a synthetic somatostatin analogue and is available as slow-release microparticle (every 7–14 days) and prolonged-release liquid (autogel, every 28–56 days) formulations. Lanreotide autogel is a supersaturated aqueous formulation for deep subcutaneous injection and is sold in a ready-to-use prefilled syringe. This ease of use allows self or partner administration at home. This article reviews the use of lanreotide in the treatment of acromegaly and its advantages and disadvantages compared with other somatostatin analogues.